Novel Modalities in DNA Data Storage. Issue 10 (October 2021) - Lim, Cheng Kai; Nirantar, Saurabh; Yew, Wen Shan; Poh, Chueh Loo
Abstract : The field of storing information in DNA has expanded exponentially. Most common modalities involve encoding information from bits into synthesized nucleotides, storage in liquid or dry media, and decoding via sequencing. However, limitations to this paradigm include the cost of DNA synthesis and sequencing, along with low throughput. Further unresolved questions include the appropriate media of storage and the scalability of such approaches for commercial viability. In this review, we examine various storage modalities involving the use of DNA from a systems-level perspective. We compare novel methods that draw inspiration from molecular biology techniques that have been devised to overcome the difficulties posed by standard workflows and conceptualize potential applications that can arise from these advances. Highlights: Viable information storage in DNA is largely limited by cost and throughput. Advances in synthesis and sequencing are key in driving adoption. Different novel methods of storing information outside of nucleotide conversion are being explored. The key workflows are not established, giving significant room for exploration. The integration of molecular biology, engineering, and computing will drive further innovation.